ANALISIS PEMODELAN DAN PERKUATAN OUT OF PLANE DINDING RUMAH SEDERHANA TERHADAP BEBAN GEMPA - , ARIF HENDRA PRATAMA, Prof. Ir. Iman Satyarno, M.E., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The high seismic activity in Indonesia has prompted previous researchers to conduct a study regarding the out of plane reinforcement efforts of brick masonry walls through a flexural strength testing in laboratory that refers to SNI 03-4165-1996. To be able to apply the reinforced walls into the construction of house buildings in the community, first it need to known the security level of the structure to be built, through an analysis of the structure modeled with the variation of the wall that will be applied. Out of plane moments that occur on each wall will be compared with the moment capacity of each wall that obtained from the previous study, so it can be known, whether the wall is safe to applied or not. In this study, structural analysis performed using SAP 2000 program. Building that modeled is type-36 house complete with all of its structural elements. The house structure is made for 5 models, each one using wall without plaster, plastered wall without reinforcement, wall with wire mesh reinforcement, wall with strapping band reinforcement, and wall with 3 mm rebar reinforcement. The wall characteristics data inputted in the modeling are based on the results of previous studies. Hereinafter, at each structure models applied with dead load and time history quake load in the form of El Centro earthquake accelerogram that scaled according to SNI 1726 in all of Indonesia quake zones, starting from the zone with the highest seismic activity (quake zone 6), till it known in which zone, the type of wall reviewed is safe to applied in house structure. From the analysis of modeling using SAP 2000, it is known that the addition of plaster on brick masonry wall can minimize the magnitude of displacement when the structure deformed due to earthquake loads. Meanwhile, the addition of out of plane wall reinforcement, either with wire mesh, strapping band, or 3 mm rebar, did not provide a significant increasement on stiffness of structure. Reviewed from the bending moment, the addition of plaster on brick masonry wall can increase the wall security very significantly. Without plaster, brick masonry wall only safely applied in the quake zone 4 on the hard soil and medium soil type and in the quake zone 5 on the hard soil type. However, when plaster added, wall become safe to applied around the earthquake area on all types of soil. Meanwhile, the addition of reinforcement materials does not have a significant effect on improving the security of brick masonry walls. Either with or without reinforcement, plastered brick masonry wall is safely applied to the house structure around the Indonesia earthquake area on all types of soil.